PENGARUH KUALITAS ARGUMEN DAN KREDIBILITAS SUMBER TERHADAP NIAT PEMBELIAN YANG DIMEDIASI OLEH KEGUNAAN INFORMASI - Waisnawa, Ni Luh Putu Ayu Yoceilla; Rastini, Ni Made (E-Jurnal Manajemen; Vol 9 No 4 (2020)DO - 10.24843/EJMUNUD.2020.v09.i04.p15, 2020)
Purchase intention is information and knowledge of prospective consumers about a particular product or service. This study aims to explain the effect of argument quality and source credibility on purchase intentions mediated by information usefulness on Wardah lipsticks in Denpasar. This research was conducted in Denpasar, Bali using non probability sampling techniques with purposive sampling, taking respondents as many as 100 people through questionnaires. Data analysis technique used descriptive statistics, path analysis, and sobel tests. Based on the results of the analysis found the argument quality and the source credibility has a positive and significant effect on the information usefulness and purchase intentions. This shows that the better the quality of the content and the more credible the sources, the more useful the information will be delivered so that the higher the purchase intention of the prospective consumer. The information usefulness mediates positively and significantly the relationship between the argument quality and the source credibility against purchase intentions. The results of the analysis obtained from the two analytical techniques show that positively and significantly the information usefulness is able to mediate the relationship between the argument quality and the source credibility of purchase intentions on Wardah lipsticks in Denpasar. Keywords : information usefulness, source credibility, argument quality, purchase intentions